2019
DOI: 10.1093/ofid/ofz242
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Genotyping of Coxiella burnetii Endocarditis in a Patient with Prosthetic Pulmonary Valve Replacement Using Next-Generation Sequencing of Plasma Microbial Cell-Free DNA

Abstract: Determining the causative etiology of culture-negative endocarditis can be challenging. We performed next-generation sequencing of plasma microbial cell-free DNA to facilitate rapid diagnosis and genotyping of Coxiella burnetii in a patient with culture-negative endocarditis of a prosthetic pulmonary valve, enabling early targeted treatment prior to valve replacement surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…They call this "cell free" DNA based on the terminology used in human clinical genomics. There have been a few case reports showing utility for the diagnosis of culture-negative endocarditis and invasive Mycobacterium chimaera disease [71,72]. In a single center clinical study looking at results of this test sent from children with a variety of indications, Rossoff et al found a 70% positivity rate [73].…”
Section: Next-generation Sequencing and Clinical Metagenomicsmentioning
confidence: 99%
“…They call this "cell free" DNA based on the terminology used in human clinical genomics. There have been a few case reports showing utility for the diagnosis of culture-negative endocarditis and invasive Mycobacterium chimaera disease [71,72]. In a single center clinical study looking at results of this test sent from children with a variety of indications, Rossoff et al found a 70% positivity rate [73].…”
Section: Next-generation Sequencing and Clinical Metagenomicsmentioning
confidence: 99%
“…In our setting, the NGS was performed in a private laboratory with the cost of RMB 4,500 (~698 USD) per sample and the turn-around-time for these two cases were two days, making the use of this robust technology pragmatic and affordable in the clinical setting. It is of note that Q fever has been diagnosed a few times using NGS in the literature [ 20 ā€“ 22 ], including a recent outbreak in southern China [ 21 ]. In that outbreak, plasma samples from 138 out of 2382 patients who had fever of unknown source were tested positive for C .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research reported an epidemic of Q fever confirmed by mNGS in 2018-2019 in Zhuhai city (29). Besides, Maiko's study conducted next-generation sequencing of plasma microbial cellfree DNA on a patient with prosthetic pulmonary valve culturenegative endocarditis to quickly diagnosis and genotyping of C. burnetii, to ensure early targeted therapy before valve replacement surgery (30). Furthermore, Huang et al (31) has reported a case of tick-transmitted Q fever diagnosed by nextgeneration sequencing in Lishui, China, which lacks serological verification.…”
Section: Discussionmentioning
confidence: 99%